KORESPONDENSI FONEM AUSTRONESIA DALAM BAHASA MELAYU JAMBI: Telaah Komparatif Terhadap Isolek Melayu Jambi Seberang dan Isolek Melayu Bungo - Dodi Oktariza; Sufiyandi Sufiyandi (Krinok:Jurnal Linguistik Budaya, 2017)
This research is aimed at: 1) describing the sound correspondence set of two languages; 2) describing kinds of proto phonemes pattern in Jambi Malay  and Bungo Malay IsolectThere are three steps conducted in the research, they are collecting data, analyzing data, and presenting the result of analysis. In collecting data, the writer used observational method by applying the elicitation technique, which is continued by several techniques, i.e  facing conversation, taking note, and recording technique. In analyzing data, the writer also used qualitative and quantitative approaches. Qualitative approach is used in order to show the sound correspondence between twi isolects. Then, the comparative method is used to compare  and determine the inheretence pattern toward two isolecst.The result of analysis are: 1) there are two of sound correspondences rules that mostly found in ultima and penultima position. namel  r ~ R /- η # /and  ə ~ ə /# b – In addition, inherited linearly, inherited with changes, and linearly with lost. The linearly inherited can be seen from some vocal of protolanguage, /*i/, /*a/, /*ə/  also consonant /*b/, /*l/, /*m/, /*p/, /*g/, /*s/, /*η/, /*k/, /*h/.Furthermore, dealing with Proto Austronesia language, it is also found that some proto phonemes are showing the alteration, namely innovation.  Key Words:      Correspondences, Proto-Austronesia, Jambi Malay, Bungo Malay